Redefining the role of IL-18 in post-surgical recovery and sepsis: a key mediator of inflammation resolution - Ioanna Papatheodorou; Gabriela Blažková; Veronika Bosáková; Zuzana Tomášiková; Erin Spearing; Robin Klieber; Pavel Ostašov; Julie Štíchová; Martina Dvončová; Alexandra Mýtniková; Jan Emmer; Kamila Bendíčková; et al. (Journal of Translational Medicine)
Abstract Background Timely resolution of innate immune responses activated by surgical intervention is crucial for patient recovery. While cytokines and innate immune cells are critical in inflammation resolution, the specific role of IL-18 in these processes remains controversial and underexplored. Methods We investigate determinants of successful recovery using peripheral blood samples from orthopedic surgery (ORT) patients (n = 33) at T0 (before surgery), T1 (24 h after surgery) and T2 (3 days after surgery). Monocytes from ORT patients underwent immunophenotyping together with bulk transcriptomic analysis. We found that IL-18 strongly defines the recovery immune signature. These results were further validated in vitro by comparing IL-18 and TNF-α effects on monocytes, and in 3D human intestine organoids together with single cell (sc)-RNAseq analysis. Results Transcriptomics of ORT monocytes revealed upregulation of ITG family integrins, namely ITGB3 and ITGB5, CXCL family chemokines, notably CXCL1-3, CXCL5, and SCL/TAL1 factor controlling differentiation and migration, but not pro-inflammatory genes. Similar changes were observed in IL-18 stimulated healthy donor monocytes in vitro, including an increase in CD11b, CD64, and CD86 levels, accompanied by increased phosphorylation of Akt but not NFκB. These changes were attenuated in the presence of TNF-α, thus showing a unique role of IL-18 when acting alone without its most frequent paired cytokine TNF-α. We further confirmed that IL-18 induces monocyte-macrophage transition and migration using human intestinal organoids. Finally, TNF-α/IL-18 ratio showed a high predictive value of clinical severity in septic patients. Conclusions We propose a novel role of IL-18 on monocyte migration and macrophage transition characterizing successful orthopedic surgery recovery, as well as the ratio of IL-18/TNF-α as a novel marker of inflammation resolution, with potential implications for patient monitoring and therapeutic strategies.